The effect of continuous interscalene brachial plexus block for arthroscopic rotator cuff repair - Tomohiro Uno; Nariyuki Mura; Issei Yuki; Ryuta Oishi; Michiaki Takagi (Elsevier, 2024)
Background: Arthroscopic rotator cuff repair (ARCR) is a minimally invasive surgical technique. However, it is challenging to control postoperative pain. This study aimed to investigate the difference between a single-shot interscalene block and a combined continuous block for ARCR. Methods: Ninety-four patients who underwent ARCR were included in this study. In the preceding period, 43 patients received a single-shot interscalene block and continuous postoperative intravenous opioid infusion (Single group). In the posterior period, 51 patients received a single-shot interscalene block preoperatively and a continuous block postoperatively (Continuous group). Their mean age at surgery was 64.9 years (range, 43-83 years). The mean follow-up period was 25.4 months (range, 24-54 months). The numerical rating scale (NRS) of pain was evaluated immediately after the surgery, at rest, and at night for 1-4 days after the surgery. One day postoperatively, the amount of food taken was assessed from 0 % (no food intake) to 100 % (all food taken). The University of California at Los Angeles (UCLA) shoulder score, range of motion (ROM), and isometric shoulder strength were evaluated. Results: NRS at rest in the Continuous group on the day of surgery was 3.7 ± 2.5. This was significantly lower than in the Single group (5.2 ± 1.8) (P = 0.002). NRS at rest in the Continuous group on the second day after surgery was 3.0 ± 2.1, significantly lower than in the Single group (3.9 ± 1.8) (P = 0.04). The amount of food taken in the morning in the Continuous group was 61 % ± 37 %, which was significantly greater than in the Single group (35 % ± 41 %) (P = 0.004). The ROM of extension at 6 months postoperatively in the Continuous group was 47 ± 7°, which was significantly greater than in the Single group (43 ± 6°) (P = 0.02). The postoperative strength of the external rotator at 6 months in the Continuous group was 95 ± 33 N, significantly greater than in the Single group (78 ± 28 N) (P = 0.01). There was no significant difference in UCLA score at any time. Conclusion: The continuous interscalene block with ultrasound guidance in ARCR effectively relieved pain. The recovery of ROM for extension and the strength of the external rotator was better in the Continuous group.